Detection of Arabic Terrorism Keyword in Websites - et. al., Arief Rahmana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents a detection technique for cyberterrorist suspected activities in the websites by using Krill Herd and Simulated Annealing algorithms. There were 1,700 dataset used with 10 cross-validation for training and testing from Tawhid, Islamion and Alemarah News websites. Based on the experiment conducted, this proposed detection technique has produced 84.9% accuracy rate, which has outperformed with the benchmark work. This paper could be used as guidance other researchers with the same interest.